Developing Rods Transplanted into the Degenerating Retina of Crx‐Knockout Mice Exhibit Neural Activity Similar to Native Photoreceptors123. (22nd May 2013) - Homma, Kohei; Okamoto, Satoshi; Mandai, Michiko; Gotoh, Norimoto; Rajasimha, Harsha K.; Chang, Yi‐Sheng; Chen, Shan; Li, Wei; Cogliati, Tiziana; Swaroop, Anand; Takahashi, Masayo
Abstract Replacement of dysfunctional or dying photoreceptors offers a promising approach for retinal neurodegenerative diseases, including age‐related macular degeneration and retinitis pigmentosa. Several studies have demonstrated the integration and differentiation of developing rod photoreceptors when transplanted in wild‐type or degenerating retina; however, the physiology and function of the donor cells are not adequately defined. Here, we describe the physiological properties of developing rod photoreceptors that are tagged with green fluorescent protein (GFP) driven by the promoter of rod differentiation factor, Nrl. GFP‐tagged developing rods show Ca2 + responses and rectifier outward currents that are smaller than those observed in fully developed photoreceptors, suggesting their immature developmental state. These immature rods also exhibit hyperpolarization‐activated current (Ih) induced by the activation of hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels. When transplanted into the subretinal space of wild‐type or retinal degeneration mice, GFP‐tagged developing rods can integrate into the photoreceptor outer nuclear layer in wild‐type mouse retina and exhibit Ca2 + responses and membrane current comparable to native rod photoreceptors. A proportion of grafted rods develop rhodopsin‐positive outer segment‐like structures within 2 weeks after transplantation into the retina of Crx‐knockout mice and produce rectifier outward current and Ih upon membrane depolarization and hyperpolarization. GFP‐positive rods derived from induced pluripotent stem (iPS) cells also display similar membrane current Ih as native developing rod photoreceptors, express rod‐specific phototransduction genes, and HCN‐1 channels. We conclude that Nrl‐promoter‐driven GFP‐tagged donor photoreceptors exhibit physiological characteristics of rods and that iPS cell‐derived rods in vitro may provide a renewable source for cell‐replacement therapy. STEM Cells2013;31:1149–1159